Ring-Strain-Driven Catalytic Carbene Formation–Cyclopropanation–Aza-Cope Rearrangement Cascade: A Facile Entry to Fused Dihydroazepines from 1,3-Dienyltriazoles - Xu, Hua-Dong; Xu, Ke; Zhou, Hao; Jia, Zhi-Hong; Wu, Hao; Lu, Xiao-Long; Shen, Mei-Hua (Synthesis, 2015)
A practical method for a facile entry to structurally unique ring-fused dihydroazepine has been developed using 1-sulfonyl-1,3-dienyltriazole as starting materials. Driven by ring strain release of cyclopropyl group, a rhodium-catalyzed α-imino carbenoid formation–cyclopropanation–aza-Cope rearrangement cascade takes place efficiently in a single operation. Substitution effects on yield and diastereoselectivity are also explored.
Keywords: carbenes; bicyclic compounds; heterocycles; cyclization; rearrangement